Breath and Smoke : Tobacco Use among the Maya - Eppich, Keith, 1971-; Loughmiller-Cardinal, Jennifer A., 1976- (Book collections on Project MUSE., 2019)
"From Classical antiquity to the present, tobacco has existed as a potent ritual substance. Tobacco use among the Maya straddles a recreational/ritual/medicinal nexus that can be difficult for Western audiences to understand. To best characterize the pervasive substance, this volume assembles scholars from a variety of disciplines and specialties to discuss tobacco in modern and ancient contexts. The chapters utilize research from archaeology, ethnography, mythic narrative, and chemical science from the eighth through the twenty-first centuries. Breath and Smoke explores the uses of tobacco among the Maya of Central America, revealing tobacco as a key topic in pre-Columbian art, iconography, and hieroglyphics. By assessing and considering myths, imagery, hieroglyphic texts, and material goods, as well as modern practices and their somatic effects, this volume brings the Mayan world of the past into greater focus and sheds light on the practices of today"--